2016
DOI: 10.1590/1808-057x201612300
|View full text |Cite
|
Sign up to set email alerts
|

Empirical analysis of Brazilian banks' capital buffers during the period 2001-2011

Abstract: International literature indicates that the capital buffers held by banks result notably from the trade-off that exists between the cost of holding capital, adjustment costs, and bankruptcy costs, which all have a direct impact on banks' capital structures. The aim of this paper is to study the degree of sensitivity of Brazilian banks' capital buffers to the determining factors established in the literature, by using a sample of 121 banks, covering the period from 2001 to 2011. The empirical analysis that was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Bank profitability affects the capital buffer because the higher the bank's profit, the more it provides an opportunity to increase the capital buffer, because part of the profit earned will be set aside as retained earnings and will be accumulated in its own capital, thereby increasing the capital buffer. Like the findings of Belém and Gartner (2016) in Brazil and Haryanto and Indonesia (2015) in Indonesia, profitability affects the capital buffer. However, the findings of Noreen et al (2016) found a significant and negative effect between profitability as measured by ROA on capital buffer.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Bank profitability affects the capital buffer because the higher the bank's profit, the more it provides an opportunity to increase the capital buffer, because part of the profit earned will be set aside as retained earnings and will be accumulated in its own capital, thereby increasing the capital buffer. Like the findings of Belém and Gartner (2016) in Brazil and Haryanto and Indonesia (2015) in Indonesia, profitability affects the capital buffer. However, the findings of Noreen et al (2016) found a significant and negative effect between profitability as measured by ROA on capital buffer.…”
Section: Introductionmentioning
confidence: 61%
“…Thus, the high profit will increase the capital buffer. In Brazil, the results of research between profitability and capital buffer shows a positive and significant effect (Belém & Gartner, 2016). Haryanto (2015) and Masood et al (2013), who conducted a study in Indonesia, also found the same thing.…”
Section: Profitability Against Capital Buffermentioning
confidence: 80%
See 2 more Smart Citations
“…Belem and Gartner [10] conducted similar studies for the Brazilian banks. They investigated the relationship between bankruptcy cost and a large number of factors.…”
Section: Literature Reviewmentioning
confidence: 96%